1999
DOI: 10.1074/jbc.274.34.23901
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Protein Kinase Pathways Are Involved in Gastrin-releasing Peptide Receptor-regulated Secretion

Abstract: Gastrin-releasing peptide (GRP) and its

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 46 publications
(39 reference statements)
1
53
0
Order By: Relevance
“…Involvement of Ca 2 þ /Cn signaling pathway in BBS-mediated upregulation of Cox-2 expression Agonist binding to GRP-R results in the rapid release of Ca 2 þ from inositol 1,4,5-triphosphate-sensitive stores (Hellmich et al, 1999). To test whether BBS induced an increase in [Ca 2 þ ] i , Caco-2 cells were loaded with the Ca 2 þ indicator dye Fura-2/AM and stimulated with BBS (100 nM) in the presence or absence of the BBS antagonist RC-3940-II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of Ca 2 þ /Cn signaling pathway in BBS-mediated upregulation of Cox-2 expression Agonist binding to GRP-R results in the rapid release of Ca 2 þ from inositol 1,4,5-triphosphate-sensitive stores (Hellmich et al, 1999). To test whether BBS induced an increase in [Ca 2 þ ] i , Caco-2 cells were loaded with the Ca 2 þ indicator dye Fura-2/AM and stimulated with BBS (100 nM) in the presence or absence of the BBS antagonist RC-3940-II.…”
Section: Resultsmentioning
confidence: 99%
“…Agonist-induced changes in [Ca 2 þ ] i were detected using the Ca 2 þ -sensitive dye Fura-2/AM as described by Hellmich et al (1999). Briefly, cell monolayers at 80% confluence were trypsinized, washed and then loaded with 1 mM Fura-2/AM under continuous stirring for 30 min at 371C.…”
Section: Intracellular Calcium Measurementsmentioning
confidence: 99%
“…When a cell is activated either by membrane depolarization or through a ligand-activated cell surface receptor such as CCK 2 of adenylyl cyclase and phospholipases (9,10). Several studies have documented the dependence of specific gene expression, secretion, and cell proliferation on the amplitude, duration, and spacial pattern of change in [Ca 2ϩ ] i (11,13,41). Dolmetsch and co-workers demonstrated the differential activation of the proinflammatory transcriptional regulator nuclear factor-B, c-Jun N-terminal kinase, and nuclear factor of activated T-cells in B lymphocytes when the amplitude and duration of change in [Ca 2ϩ ] i was manipulated with ionomycin and Ca 2ϩ chelator EGTA (11).…”
Section: Discussionmentioning
confidence: 99%
“…Small differences in the amplitude, duration, and/or temporal pattern of change in [Ca 2ϩ ] i can have profound effects on cell physiology, altering programs of gene expression (11,12), secretory activity (13), cell proliferation, and survival (14 -16). Calcium is an essential signaling molecule in G17-stimulated cell proliferation.…”
mentioning
confidence: 99%
“…Moreover, we [22] found that the addition of 1-oleoyllysophosphatidic acid to rat ascites hepatoma cells resulted in an instantaneous increase in intracellular calcium, but when these cells were pretreated with the antimetastatic agent, ginsenoside Rg3, the intracellular calcium spike induced by 1-oleoyl-lysophosphatidic acid was completely abolished. Hellmich et al [23] found that bombesin induced either intracellular calcium oscillations or biphasic elevation in intracellular calcium, and that the activation of mitogen-activated protein kinase (MAPK) kinase (MEK) was important for maintaining the elevated intracellular calcium levels induced by bombesin. The MAPK-MEK cascade was closely related to the tumor cell invasion [24].…”
Section: Discussionmentioning
confidence: 99%